2008
DOI: 10.2166/wst.2008.520
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic codigestion of the mechanically sorted organic fraction of a municipal solid waste with cattle manure in packed microcosms under batch conditions

Abstract: Packed microcosms, consisting of 0.6 L-flask filled with tire chips (TC, a non-cost-recyclable non-biodegradable material) or ceramic cubes, were employed in the wet batch mesophilic anaerobic codigestion of a mechanically sorted organic fraction of a municipal solid waste with cattle manure. Two different waste mixtures were digested within four successive batch experiments, performed by collecting the digested waste and by refilling each microcosm with the same experimental mixture. Methane production yields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The development of effective AD processes able to biomethanize wet MS‐OFMSW would contribute to promote the separation of wet and dry fractions of MSW: this approach can significantly increase the waste treatment effectiveness, since the disposal of dried matter would allow higher combustion efficiencies or lower waste amounts to be dumped if incineration or landfilling, respectively, are applied as the treatment procedure. However, most studies were related to co‐digestion processes, in which MS‐OFMSW was fed to the digester together with remarkable amounts of highly digestible co‐substrates,4–6 whereas few successful examples of direct AD of MS‐OFMSW have been reported in the literature 7–14. Furthermore, all these studies were carried out under batch conditions, often in the presence of recirculated leachate, with, to the very best of our knowledge, a lack of data related to effective AD (semi)continuous processes dedicated to the direct digestion of MS‐OFMSW occurs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of effective AD processes able to biomethanize wet MS‐OFMSW would contribute to promote the separation of wet and dry fractions of MSW: this approach can significantly increase the waste treatment effectiveness, since the disposal of dried matter would allow higher combustion efficiencies or lower waste amounts to be dumped if incineration or landfilling, respectively, are applied as the treatment procedure. However, most studies were related to co‐digestion processes, in which MS‐OFMSW was fed to the digester together with remarkable amounts of highly digestible co‐substrates,4–6 whereas few successful examples of direct AD of MS‐OFMSW have been reported in the literature 7–14. Furthermore, all these studies were carried out under batch conditions, often in the presence of recirculated leachate, with, to the very best of our knowledge, a lack of data related to effective AD (semi)continuous processes dedicated to the direct digestion of MS‐OFMSW occurs.…”
Section: Introductionmentioning
confidence: 99%
“…This evidence can be mostly ascribed to the poor efficiency of AD towards MS‐OFMSW organic matter, which is mainly due to the occurrence of heavy metals and organics able to adversely affect key constituents of the microbial community carrying out the process 15. Recent studies have shown that the inhibition of methane production due to MS‐OFMSW pollutants can be mitigated via tailored acclimation of the AD microbial community to the MS‐OFMSW 5, 16. The selection of robust pollutant‐resistant AD microbial community can be achieved through a dedicated enrichment procedure applied to a MS‐OFMSW native microflora grown in the presence of an organic matter‐rich biowaste, such as cattle manure (CM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a high performing MS-OFMSW biomethanizating consortium was obtained via a dedicated enrichment procedure. To this aim, a 0.36 L upflow anaerobic reactor supplied with a recycle line was developed and filled with cattle manure (2.2% w/w of VSS, 6.2 g/L of COD), which was demonstrated to be an effective co-substrate for the biomethanization of MS-OFMSW (Bertin et al, 2008). After a short batch period, the reactor was fed with MS-OFMSW diluted with its leachate through a repeated batch scheme.…”
mentioning
confidence: 99%
“…Co-digestion approach can represent a feasible solution since it combines the pollutant dilution to microbial nutrients supplying; particularly, cattle manure was demonstrated to be a performing co-substrate (Bertin et al, 2008). On the other hand, lower MS-OFMSW loads can so be processed.…”
mentioning
confidence: 99%